A cautionary tale of false-negative nasopharyngeal COVID-19 testing. (2020) - Bullis, Sean S.M.; Crothers, Jessica W.; Wayne, Shawn; Hale, Andrew J.
Abstract: There remains diagnostic uncertainty regarding the sensitivity of reverse transcription polymerase chain reaction in detection of SARS-CoV-2 from nasopharyngeal specimens. We present a case where two nasopharyngeal specimens were negative, followed by a positive sputum sample. Serial testing for COVID-19 is indicated in patients with high pretest probability of disease.